Electrical stimulation mapping in the medial prefrontal cortex induced auditory hallucinations of episodic memory: A case report - Long, Qiting; Li, Wenjie; Zhang, Wei; Han, Biao; Chen, Qi; Shen, Lu; Liu, Xingzhou (Frontiers in Human Neuroscience, 2022)
It has been well documented that the auditory system in the superior temporal cortex is responsible for processing basic auditory sound features, such as sound frequency and intensity, while the prefrontal cortex is involved in higher-order auditory functions, such as language processing and auditory episodic memory. The temporal auditory cortex has vast forward anatomical projections to the prefrontal auditory cortex, connecting with the lateral, medial, and orbital parts of the prefrontal cortex. The connections between the auditory cortex and the prefrontal cortex thus help in localizing, recognizing, and comprehending external auditory inputs. In addition, the medial prefrontal cortex (MPFC) is believed to be a core region of episodic memory retrieval and is one of the most important regions in the default mode network (DMN). However, previous neural evidence with regard to the comparison between basic auditory processing and auditory episodic memory retrieval mainly comes from fMRI studies. The specific neural networks and the corresponding critical frequency bands of neuronal oscillations underlying the two auditory functions remain unclear. In the present study, we reported results of direct cortical stimulations during stereo-electro-encephalography (SEEG) recording in a patient with drug-resistant epilepsy. Electrodes covered the superior temporal gyrus, the operculum and the insula cortex of bilateral hemispheres, the prefrontal cortex, the parietal lobe, the anterior and middle cingulate cortex, and the amygdala of the left hemisphere. Two types of auditory hallucinations were evoked with direct cortical stimulations, which were consistent with the habitual seizures. The noise hallucinations, i.e., “I could hear buzzing noises in my head,” were evoked with the stimulation of the superior temporal gyrus. The episodic memory hallucinations “I could hear a young woman who was dressed in a red skirt saying: What is the matter with you?,” were evoked with the stimulation of MPFC. The patient described how she had met this young woman when she was young and that the woman said the same sentence to her. Furthermore, by analyzing the high gamma power (HGP) induced by direct electrical stimulation, two dissociable neural networks underlying the two types of auditory hallucinations were localized. Taken together, the present results confirm the hierarchical processing of auditory information by showing the different involvements of the primary auditory cortex vs. the prefrontal cortex in the two types of auditory hallucinations.